2001
DOI: 10.2337/diabetes.50.10.2344
|View full text |Cite
|
Sign up to set email alerts
|

Increased Lactate Release per Fat Cell in Normoglycemic First-Degree Relatives of Individuals With Type 2 Diabetes

Abstract: The aim of this study was to examine subcutaneous lactate production in the relatives of individuals with type 2 diabetes. Therefore, we recruited seven healthy first-degree relatives of type 2 diabetic patients and seven pairwise, matched, healthy control subjects without any heredity for diabetes. All subjects were studied with a euglycemic insulin clamp at ϳ600 pmol/l, abdominal subcutaneous microdialysis, and 133 Xe clearance. Furthermore, a subcutaneous needle biopsy was performed to determine fat cell si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 64 publications
(71 reference statements)
0
15
0
Order By: Relevance
“…In vivo lactate release from subcutaneous abdominal adipose tissue has previously been found to be higher in FDR rthan in CON (47), and these findings suggest that an increased uptake and turnover of glucose in adipose tissue is a primary defect in the development of type 2 diabetes. Furthermore, Eriksson et al (14) found less efficient inhibition of in vivo lipolysis by insulin in subcutaneous abdominal adipose tissue of FDR compared with CON, and it thus seems that subcutaneous abdominal adipose tissue metabolite turnover (glucose, lactate, lipids) in general is increased in FDR.…”
Section: Adipose Tissue and Skeletal Muscle Metabolismmentioning
confidence: 78%
“…In vivo lactate release from subcutaneous abdominal adipose tissue has previously been found to be higher in FDR rthan in CON (47), and these findings suggest that an increased uptake and turnover of glucose in adipose tissue is a primary defect in the development of type 2 diabetes. Furthermore, Eriksson et al (14) found less efficient inhibition of in vivo lipolysis by insulin in subcutaneous abdominal adipose tissue of FDR compared with CON, and it thus seems that subcutaneous abdominal adipose tissue metabolite turnover (glucose, lactate, lipids) in general is increased in FDR.…”
Section: Adipose Tissue and Skeletal Muscle Metabolismmentioning
confidence: 78%
“…All buffers and media were adjusted to pH 7.4. After 24 h of resting, cells were incubated with or without glucose at different concentrations (5.0, 8.3 and 11.1 mmol/l) for up to 4 h. Further co-incubations with standard concentrations of insulin (600 pmol/l) [13] and the phosphatidylinositol 3-kinase (PI3-kinase) inhibitor wortmannin (100 nmol/l) [14], protein kinase B (AKT) inhibitor (10 μmol/l) [15] (both Alexis, Lausen, Switzerland) and insulin-receptor antibody (20 nmol/l, Ab 3; Labvision, Fremont, CA, USA) [16] were tested. Supernatants of the culture media were stored and analysed for visfatin concentrations.…”
Section: Cell Culture Experimentsmentioning
confidence: 99%
“…Although AT is of minor quantitative importance for whole-body glucose disposal, the tissue produces lactate (11), which functions as a gluconeogenic precursor in the liver (12). Previous studies have demonstrated increased plasma lactate (13) and lactate release from adipocytes (14) in FDR subjects.…”
mentioning
confidence: 99%